Effect of Helicobacter pylori infection on outcomes in resected gastric and gastroesophageal junction cancer - Kolb, Jennifer M.; Ozbek, Umut; Harpaz, Noam; Holcombe, Randall F.; Ang, Celina (Journal of Gastrointestinal Oncology; Vol 8, No 3 (June 23, 2017): Journal of Gastrointestinal Oncology (Novel Biologics In Era of Precision Medicine)1, 2017)
Background: Helicobacter pylori (H pylori) infection is a known risk factor for gastric cancer (GC) and has been linked with gastroesophageal junction (GEJ) cancer. Studies examining the relationship between H. pylori infection, GC characteristics and prognosis are limited and have yielded conflicting results. We report on the clinicopathologic characteristics and oncologic outcomes of gastric and GEJ cancer patients with and without a history of H. pylori treated at our institution. Methods: We retrospectively reviewed the medical records of patients over the age of 18 years who underwent curative resection for GEJ and GC at Mount Sinai Hospital between 2007 and 2012 who had histopathologic documentation of the presence or absence of H pylori infection. Demographic, clinical, pathologic, treatment characteristics and outcomes including recurrence-free survival (RFS) and overall survival (OS) were compared. Results: Ninety-five patients were identified. The majority of patients were male (61%), white (36%) or Asian (34%), with median age at diagnosis 64. Tumors were stage I (51%), stage II (23%), stage III (25%), and stage IV (1%). H pylori infection status was documented at the time of cancer diagnosis in 89 (94%) patients, and following cancer diagnosis and treatment in 6 (6%) patients. Younger age at diagnosis, Asian race and Lauren histologic classification were associated with H Pylori infection. H pylori positive patients exhibited higher 5-year OS and 5-year RFS compared to H pylori negative patients, though the difference was not statistically significant in either univariate or multivariate analyses. Conclusions: In this retrospective series of predominantly early stage GC and GEJ cancers, H. pylori positive patients were significantly younger at cancer diagnosis and were more frequently Asian compared to H. pylori negative patients. Other demographic and histologic classifications except for Lauren histologic classification were similar between the two groups. H pylori positive patients appeared to have improved outcomes compared to H. pylori negative patients.